Fulminant Peripartum Pulmonary Embolism Leads To Maternal Cardiac Arrest And Hypoxic-ischemic Encephalopathy - Muhamad Rafiqi Hehsan; Muhammad Faris 'Imadi Mohd Saidi; Melor Mohd Mansor; Mohd Sany Shoib (APICARE publication, 2024)
Indexed by WOS/ Scopus